A GaN‐Based VCSEL with a Convex Structure for Optical Guiding. Issue 10 (20th February 2018) - Hayashi, Natsumi; Ogimoto, Junichiro; Matsui, Kenjo; Furuta, Takashi; Akagi, Takanobu; Iwayama, Sho; Takeuchi, Tetsuya; Kamiyama, Satoshi; Iwaya, Motoaki; Akasaki, Isamu
Abstract : In this paper, room‐temperature continuous‐wave operation of a GaN‐based vertical‐cavity surface‐emitting laser (VCSEL) with a convex structure for optical guiding is demonstrated. The GaN‐based VCSEL is designed and fabricated with the convex structure containing a 15‐nm step between the center area and the peripheral area of the VCSEL with a Nb2 O5 spacer layer. In theory the convex structure with a 1.5% relative refractive index difference between the areas could provide more than 10 high‐order modes. Experimental emission spectra and near field pattern images clearly suggested a multi‐mode operation of the VCSEL with the convex structure. In addition, the VCSEL shows a lower threshold current, 2 mA, and a higher maximum light output power, 0.88 mW, which are superior to those of our standard VCSEL fabricated simultaneously without the convex structure. These results indicate that the optical guiding with the convex structure plays an important role in developments of GaN‐based VCSELs. Abstract : A GaN‐based vertical‐cavity surface‐emitting laser (VCSEL) formed with a spacer layer is designed and fabricated. The convex structure with a 15‐nm step between center and peripheral area could result in a relative refractive index difference of 1.5%. Room‐temperature continuous‐wave operation of the VCSEL is demonstrated, showing a lower threshold current and a multi‐mode operation. Thus, the convex structure for optical guiding plays an important role in the development of high‐performance GaN‐based VCSELs.